2009
DOI: 10.2478/10004-1254-60-2009-1908
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effects of Quercetin and Ethanolic Extract of Propolis in Gamma-Irradiated Mice

Abstract: The aim of this study was to assess radioprotective effects of quercetin and the ethanolic extract of propolis (EEP) in CBA mice exposed to a single radiation dose 4 Gy ( 60 Co). The mice were treated with 100 mg kg -1 quercetin or EEP a day for three consecutive days either before (pre-treatment) or after gamma-irradiation (therapy). Leukocyte count was determined in blood drawn from the tail vein, and DNA damage in leukocytes was assessed using the alkaline comet assay. Genotoxic effects of the test compunds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
(52 reference statements)
1
34
0
6
Order By: Relevance
“…Quercetin has been used as pre-treatment to radiation in mice (16) and other flavonoids have been tested both prior to and following irradiation (17). The present study has demonstrated the radiomitigative effects of quercetin when administered for four days prior to and six days following whole-body X-irradiation.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Quercetin has been used as pre-treatment to radiation in mice (16) and other flavonoids have been tested both prior to and following irradiation (17). The present study has demonstrated the radiomitigative effects of quercetin when administered for four days prior to and six days following whole-body X-irradiation.…”
Section: Discussionmentioning
confidence: 70%
“…Quercetin has been successfully tested as an antioxidant in several in vitro studies using cell cultures (16,39,40), but its in vivo activity has been questioned. Studying vitamin E-deficient rats supplemented with vitamin E or a variety of flavonoids, including quercetin, Duthie et al (41) concluded that in vivo supplementation with these antioxidant compounds (100 mg/kg diet) is ineffective in restoring lipid peroxidation indices in plasma and liver.…”
Section: Discussionmentioning
confidence: 99%
“…All of these compounds are responsible for its biological and pharmacological properties. [14][15][16][17] According to pharmacological characteristics of propolis and lack of data about its effects on salivary glands as well as its reasonable price and good historical safety profile, we decided to use propolis in our study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that between them, the constituents with major contribution in the radioprotective effect are the flavonoids. Some of the radioprotective mechanisms are scavenger potency against free radicals [30], immunological properties [10], protection against inflammatory responses [9], protection against fetal effects of radiation, and apoptosis in cancer cells [2]. Moreover, Kunimasa et al [24] have demonstrated that flavonoids have antioxidative potency in vitro and in vivo, protect mice against lethal effects of whole-body irradiation, and diminish primary DNA damage [4].…”
Section: Discussionmentioning
confidence: 99%
“…Propolis has shown protect against the induction of apoptosis by radiation; since it is an imunomodulator, it has antioxidative and cytotoxic activities, antitumor activities, and scavenges free radicals produced by the indirect effect of ionizing radiation [2,[7][8][9][10][11][12]. Moreover, several reports have demonstrated the ability of EEP to protect mice against gamma irradiation preventing exaggerated inflammatory response [9], promoting high survival in mice [10], protecting their whole blood cells, and also diminishing primary DNA damage in mice [4,13].…”
Section: Introductionmentioning
confidence: 99%